Peran Unsur-Unsur Pendidikan Islam dalam Membentuk Karakter Peserta Didik Menurut Pemikiran Al-Ghazali - Pusparini; Maimunah; Eny Ratna Purwanti; Ahsan Hakim (Educational Research Center, 2026)
Islamic education has the primary objective of shaping human beings with noble character who are capable of carrying out their roles as servants of Allah and caliphs on earth. From Al-Ghazali’s perspective, education is not merely a process of transferring knowledge, but also a process of purifying the soul (tazkiyatun nafs) and developing moral character. This study aims to analyze the role of the components of Islamic education in shaping students’ character based on Al-Ghazali’s educational philosophy. This research employs a qualitative method using a library research approach. The data were collected from books, journals, scientific articles, and other literature related to Islamic educational philosophy and Al-Ghazali’s thoughts. The findings reveal that the components of Islamic education, such as educational objectives, educators, students, curriculum, teaching methods, educational environment, and evaluation, are closely interconnected in shaping students’ character. According to Al-Ghazali, educators must serve as moral role models, while students are required to uphold proper manners (adab) in seeking knowledge. The curriculum of Islamic education should emphasize a balance between religious and general sciences and be directed toward the formation of noble character. Educational methods such as exemplary behavior, habituation, advice, and spiritual exercises become the primary means of character building. By implementing the components of Islamic education based on Al-Ghazali’s philosophy, students are expected to become individuals who are faithful, knowledgeable, and possess noble moral.